Relationship between the consumer price index and the producer price index for six south american countries - Cerquera Losada, Oscar Hernán; Murcia Arias, Juan Pablo; Conde Guzmán, Jonás (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (páginas 39-74).